Conversor de único estágio baseado na integração Charge-Pump Valley-Fill para acionamento de LEDs de potência - Motta, Leandro Chelski da (2017)
This work proposes a single stage electronic system to drive power LEDs employing Charge-Pump and Valley-Fill concepts. Both concepts are related to topological configurations based on the integration of an input boost rectifier with an output halfbridge inverter, characterizing the single stage system. The Charge-Pump configuration is used to decrease LEDs' current ripple. The Valley-Fill configuration is used to restrict the DC bus voltage at levels lower than the input source voltage peak value over a long period of time in the source period, keeping a high power-factor system. Thus, it is possible to use bus capacitors with reduced values. The proposed converter operation principle, which in steady-state includes three operation modes, that will be presented and analyzed. A design methodology as well as simulation results will also be presented so that the system operational characteristics can be verified. In this paperwork, the symmetric command will be used at a switching frequency of 67 KHz. The supply voltage is 220 V and the load is composed of 18 LEDs series connected with total power of 47 W.